2005
DOI: 10.1007/s11064-005-8834-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Retigabine on the Neurodegeneration and Extracellular Glutamate Changes Induced by 4-Aminopyridine in Rat Hippocampus In Vivo

Abstract: We have previously shown that microdialysis perfusion of the K+ channel blocker 4-aminopyridine (4-AP) in rat hippocampus induces convulsions and neurodegeneration, due to the stimulation of glutamate release from synaptic terminals. Retigabine is an opener of the KCNQ2/Q3-type K+ channel that possesses antiepileptic action and may be neuroprotective, and we have therefore studied its effect on the hyperexcitation, the neuronal damage and the changes in extracellular glutamate induced by 4-AP. Retigabine and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…In contrast, Rekling (2003) found that RTG/ EZG did not protect hippocampal slice cultures against oxygen/glucose deprivation, although several other AEDs tested in their model were effective. In an in vivo model of neurodegeneration induced by hippocampal administration of 4AP, RTG/EZG reduced cell loss from the cornu ammonis-1 region measured 24 h post-4-AP (Mora & Tapia, 2005). Both drugs were infused via a dialysis probe, which allowed simultaneous measurement of extracellular glutamate.…”
Section: Neuroprotectionmentioning
confidence: 99%
“…In contrast, Rekling (2003) found that RTG/ EZG did not protect hippocampal slice cultures against oxygen/glucose deprivation, although several other AEDs tested in their model were effective. In an in vivo model of neurodegeneration induced by hippocampal administration of 4AP, RTG/EZG reduced cell loss from the cornu ammonis-1 region measured 24 h post-4-AP (Mora & Tapia, 2005). Both drugs were infused via a dialysis probe, which allowed simultaneous measurement of extracellular glutamate.…”
Section: Neuroprotectionmentioning
confidence: 99%
“…Although the drug might be effective in other seizure types, the study only evaluated its effects on partial-onset seizures. The investigators found that retigabine reduced seizures in this refractory group at a rate similar to other new antiepileptic drugs (12). The data indicate that 900 mg probably will be the median dose for this drug, as it produced fewer adverse effects than the 1200-mg dose (17% for the 600 mg arm, 20.2% for the 900 mg arm, and 29.2% for the 1200 mg arm).…”
Section: Commentarymentioning
confidence: 82%
“…Retigabine is one of the most recent drugs belonging to antiepileptics and it has a unique mechanism of action associated mainly with the activation of voltage-gated potassium channels Kv7 [1]. The drug also increases GABAergic transmission, primarily through GABA A receptors [2], inhibits glutamatergic transmission [3], and if administered at high doses, it blocks voltage-gated sodium and calcium channels [4]. Results of recent research indicate that retigabine may also inhibit striatal cholinergic interneuron activity [5].…”
Section: Introductionmentioning
confidence: 99%